Current status and perspective of CAD/CAM-produced resin composite crowns: a review of clinical effectiveness - Miura, Shoko (Jpn Dent Sci Rev, 2020)
The purpose of the present review was to survey the available literature on computer-aided design/computer-aided manufacturing (CAD/CAM)-produced resin composite materials to provide clinicians with a current overview of the key components necessary for daily clinical use. An electronic search was conducted in the PubMed database. Peer-reviewed articles in English language on the use of resin composites in CAD/CAM dental crowns were included. A total of 122 full-text articles were identified, 15 of which were selected during the initial review. Two additional articles were also discovered through a manual search, to obtain a final total of 17 articles included in the present review. Of these, 16 were to in vitro studies, and one was an in vivo study. Findings from the in vitro studies indicate that resin composite block materials for CAD/CAM applications demonstrate excellent physical properties and are appropriate for the clinical restoration of premolars and molars. However, the in vivo study reported a low 3-year success rate, but high survival rate for resin composite CAD/CAM crowns placed in the premolar region. The key to ensuring the successful prognosis of a resin composite CAD/CAM crown is to ensure that all steps—such as proper case selection, abutment tooth preparation, occlusal adjustment, and bonding—are accurately performed.